IMPLEMENTASI MAUIDZAH HASANAH DALAM KEGIATAN PEMBERDAYAAN KESEJAHTERAAN KELUARGA SEBAGAI SARANA PENDIDIKAN AGAMA ISLAM DI DESA NGORO JOMBANG - Etikasari; Muhammad Abror Rosyidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of Mauidzah Hasanah within PKK activities in Ngoro Village, Jombang, as a medium for non-formal Islamic education, which has not yet been systematically organized. Using a qualitative field research approach, data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing, with validity tested through triangulation. The results indicate that Mauidzah Hasanah is conducted routinely monthly in the form of brief lectures, although its management remains unprogrammed. Nevertheless, it has been functionally effective in instilling religious values, increasing religious awareness, and strengthening the family’s role as a primary educational unit. Supporting factors include member enthusiasm, community leader support, and a strong religious culture. Conversely, the primary inhibiting factors are time constraints, monotonous delivery methods, and a lack of structured material planning. This study concludes that Mauidzah Hasanah holds significant potential as an Islamic education method in rural areas; however, it requires systematic development in both material management and methodology to ensure optimal and sustainable implementation.